The good die young - Macauley, Richard (BFI, 2020)
Vier junge unbescholtene Männer, ehemalige Kriegsteilnehmer, die in Geldnot geraten sind, unternehmen gemeinsam in London einen Raubüberfall. Eine kriminalpsychologische Studie mit genauer Charakterzeichnung. Aus dem Zusammenfließen der verschiedenen Berufs- und Eheschicksale ergibt sich ein bewegendes, hervorragend gespieltes Drama, das über die ohnehin fesselnde Kriminalgeschichte hinauswirkt. - Ab 16. [Film-Dienst]
Original: UK, 1953, ©1954 Remus Films
Original aspect ratio 1.66:1
Verlagsnummer BFIB1388
Special features: newly remastered by the BFI and presented in High Definition and Standard Definition ; "The Good Die Young" (export version)(1953, 101 mins, Blu-ray only): made available here for the first time, this extended overseas-only version of the film contains anti-establishment sentiments considered too strong for British audiences of the day ; "When Giant Fought" (1926, 31 mins): a contentious but historic boxing match of 1810 is vividly revisited in this power-packed silent drama, with a newly commissioned musical score by Mordecai Smyth ; "Midnight Taxi" (1946, 17 mins): a London cabby uncovers the city's secret nightlife in this surprising plug for post-war National Savings ; "Under Night Streets" (1958, 20 mins): after the last tube has gone, an army of underground workers get busy down below ; "Not Like Any Other Director: Lewis Gilbert" (1995, 31 mins): Michael Caine introduces the director of The Good Die Young in this excerpt from an onstage interview at London's National Film Theatre ; image gallery
Keywords: Film; Blu-Ray-Disc; DVD-Video